Loss of BAF Complex in Developing Cortex Perturbs Radial Neuronal Migration in a WNT Signaling-Dependent Manner - Sokpor, Godwin; Kerimoglu, Cemil; Nguyen, Huong; Pham, Linh; Rosenbusch, Joachim; Wagener, Robin; Nguyen, Huu Phuc; Fischer, Andre; Staiger, Jochen F.; Tuoc, Tran (Frontiers in Molecular Neuroscience, 2021)
Radial neuronal migration is a key neurodevelopmental event indispensable for proper cortical laminar organization. Cortical neurons mainly use glial fiber guides, cell adhesion dynamics, and cytoskeletal remodeling, among other discrete processes, to radially trek from their birthplace to final layer positions. Dysregulated radial migration can engender cortical mis-lamination, leading to neurodevelopmental disorders. Epigenetic factors, including chromatin remodelers have emerged as formidable regulators of corticogenesis. Notably, the chromatin remodeler BAF complex has been shown to regulate several aspects of cortical histogenesis. Nonetheless, our understanding of how BAF complex regulates neuronal migration is limited. Here, we report that BAF complex is required for neuron migration during cortical development. Ablation of BAF complex in the developing mouse cortex caused alteration in the cortical gene expression program, leading to loss of radial migration-related factors critical for proper cortical layer formation. Of note, BAF complex inactivation in cortex caused defective neuronal polarization resulting in diminished multipolar-to-bipolar transition and eventual disruption of radial migration of cortical neurons. The abnormal radial migration and cortical mis-lamination can be partly rescued by downregulating WNT signaling hyperactivity in the BAF complex mutant cortex. By implication, the BAF complex modulates WNT signaling to establish the gene expression program required for glial fiber-dependent neuronal migration, and cortical lamination. Overall, BAF complex has been identified to be crucial for cortical morphogenesis through instructing multiple aspects of radial neuronal migration in a WNT signaling-dependent manner.